2005
DOI: 10.1124/jpet.104.081075
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin (ET)-1-Induced Inhibition of ATP Release from PC-12 Cells Is Mediated by the ETBReceptor: Differential Response to ET-1 on ATP, Neuropeptide Y, and Dopamine Levels

Abstract: ABSTRACTϩ -evoked ATP release. Real-time intracellular calcium level recordings were performed on PC-12 cell suspensions, and ET-1 induced a dose-dependent decrease in the K ϩ -evoked calcium levels. Nifedipine, the L-type voltage-dependent Ca 2ϩ channel antagonist, caused inhibition of the K ϩ -stimulated ATP release, but the N-type Ca 2ϩ channel antagonist, -conotoxin GVIA, did not reverse the effect on ATP release. These data suggest that ET-1 modulates the release of ATP via the ET B receptor and its assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…In fact, these cells are known to express purinergic P2X receptors (Arthur et al, 2007), store ATP and catecholamines in dense-core vesicles (Fabbro et al, 2004), express E-NTPDase1/CD39 (Vollmayer et al, 2001), and release ATP and dopamine upon depolarization (Gardner et al, 2005). As observed before by others (Avidor et al, 1994), we noted that ATP and dopamine exocytosis in differentiated PC12 cells depends on Ca 2ϩ entry via voltage-gated Ca 2ϩ channels, particularly of the L-type.…”
Section: Discussionsupporting
confidence: 57%
“…In fact, these cells are known to express purinergic P2X receptors (Arthur et al, 2007), store ATP and catecholamines in dense-core vesicles (Fabbro et al, 2004), express E-NTPDase1/CD39 (Vollmayer et al, 2001), and release ATP and dopamine upon depolarization (Gardner et al, 2005). As observed before by others (Avidor et al, 1994), we noted that ATP and dopamine exocytosis in differentiated PC12 cells depends on Ca 2ϩ entry via voltage-gated Ca 2ϩ channels, particularly of the L-type.…”
Section: Discussionsupporting
confidence: 57%
“…There was enhancement of cellular ATP levels in PC12 cells by 2,5-dideoxyadenosine, a Psite inhibitor of adenylate cyclase [716]. Endothelin-1 inhibited the release of ATP from PC12 cells via ET B receptors by attenuation of the influx of extracellular Ca 2+ through L-type channels [717]. β-Nicotinamide adenine dinucleotide was released together with ATP and DA from PC12 cells, but probably with different sites of vesicular release [718].…”
Section: Phaeochromocytomamentioning
confidence: 91%
“…Using activation of P2Y12 receptor as a biosensor for nucleotide release, it was suggested that spontaneous nucleotide release from PC12 cells occurs independently of vesicle exocytosis, whereas depolarization-evoked nucleotide release relies predominantly on exocytosis mechanisms (Hussl et al, 2007); however, the nature of released nucleotides was not determined in this study. Gardner et al, 2005 demonstrated using HPLC-FLD that ω-conotoxin GVIA had no effect on the KCl-evoked release of ATP in PC12 cells. In addition, they showed that endothelin-1 differentially modulated the release of ATP and dopamine, suggesting different sites or mechanisms of release of these substances in PC12 cells.…”
Section: Evidence For Release Of Purine Neurotransmittersmentioning
confidence: 96%